Peningkatan Motivasi Belajar Melalui Bimbingan Belajar Secara Daring di Masa Pandemi - Agus Arswimba; Maria Margaretha Sri Hastuti (Jurnal Selaras: Kajian Bimbingan dan Konseling serta Psikologi Pendidikan, 2022)
Orphanage children are vulnerable people, we are required to improve their quality of life. The purpose of this study was to determine the effectiveness of online tutoring to increase learning motivation of Santa Maria Boro orphanage children. The methodology that will be used is Classroom Action Research. Benefits This research can be a reference or add insight related to online learning motivation guidance for orphans. The results of this study are learning motivation guidance can increase learning motivation from the initial condition of 118,321 then it rose in cycle 1 to 120,750 then rose again in cycle 2 to 121,893, but the increase was not significant. The reason for the increase is not significant because the internet network is difficult and the devices to support group guidance services are very inadequate. Keywords: orphanage children, learning motivation, online tutoring